Histopathological Features of the Gastric Mucosa in Patients with Chronic Gastritis and Helicobacter pylori Infection at Pertamina Central Hospital Jakarta - Safira, Fathi Rahmah; Sugiarto, Sugiarto (Muhammadiyah Medical Journal, 2021)
Background: Chronic gastritis is a chronic inflammation of the gastric mucosa, accompanied by changes in mucosal histology with or without Helicobacter pylori infection. Changes in the gastric mucosa include gastric mucosal atrophy, intestinal metaplasia, and epithelial dysplasia. Purposes: This study aims to determine the microscopic appearance of the mucosa in chronic gastritis patients based on standard histopathological criteria, which include gland atrophy, intestinal metaplasia, dysplasia with or without Helicobacter pylori infection at Pertamina Central Hospital Jakarta period 2018 - 2019. Methods: This retrospective study was conducted in a cross-sectional study from March 15 to March 25, 2020. Results: This study reported 303 cases of active chronic gastritis (38.4%) out of 790 total samples that met the inclusion criteria. Microscopic changes of the mucosa were found in the form of atrophy of the mucous glands in 254 cases (32.2%), intestinal metaplasia in 25 cases (3.2%), and epithelial dysplasia cases in 23 cases (2.9%). Conclusion: the proportion of active chronic gastritis patients found in this study was helicobacter pylori infection is more dominantly found in patients with active chronic gastritis than in non-active chronic gastritis. The description of atrophic glands in chronic gastritis patients was more dominant than parameters based on intestinal metaplasia and epithelial dysplasia. It was a finding of intestinal metaplasia compared to all cases showing risk factors that require further clinical observation (follow-up) to detect potential malignancies earlier so that it is necessary to do more preventive action.